2007
DOI: 10.1021/jp068963t
|View full text |Cite
|
Sign up to set email alerts
|

Fidelity of the Protein Structure Reconstruction from Inter-Residue Proximity Constraints

Abstract: Inter-residue proximity constraints obtained in such experiments as cross-linking/mass spectrometry are important sources of information for protein structure determination. A central question in structure determination using these constraints is, What is the minimal number of inter-residue constraints needed to determine the fold of a protein? It is also unknown how the different structural aspects of constraints differentiate their ability in determining the native fold and whether there is a rational strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 60 publications
(93 reference statements)
3
39
0
1
Order By: Relevance
“…A similar conclusion that present PDB data are already complete enough to solve the protein structure prediction problem has been reached using homology-based arguments [34]. It has already been shown that a small subset of distance constraints can accurately define the structure [13]. Hence the development of algorithms to define adaptive and essential subsets of constraints is the most promising way forward.…”
Section: Less Is Moresupporting
confidence: 59%
See 3 more Smart Citations
“…A similar conclusion that present PDB data are already complete enough to solve the protein structure prediction problem has been reached using homology-based arguments [34]. It has already been shown that a small subset of distance constraints can accurately define the structure [13]. Hence the development of algorithms to define adaptive and essential subsets of constraints is the most promising way forward.…”
Section: Less Is Moresupporting
confidence: 59%
“…A binary contact map describes an ensemble of protein structures as a network of contacts or distance constraints (see Box 1.). Currently, three-dimensional structures can be reconstructed from contact maps at an accuracy of approximately 2 Å Ca rmsd [13]. The result is not a single structure but, like models from NMR data, an entire ensemble of conformations consistent with the given constraints.…”
Section: The Consensus Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of some reports (Bagler and Sinha, 2007;Chen et al, 2007;Vassura et al, 2008b) propose different methods to predict amino acid interaction networks from the primary sequence. The authors try to reconstruct the protein backbones but not the entire tertiary structures.…”
Section: Discussionmentioning
confidence: 99%